Assessment of Berberine as a Multi-target Antimicrobial: A Multi-omics Study for Drug Discovery and Repositioning - SARIYAR AKBULUT, BERNA; SAYAR, NİHAT ALPAGU (MARY ANN LIEBERT, INC, 2014)
Postgenomics drug development is undergoing major transformation in the age of multi-omics studies and drug repositioning. Rather than applications solely in personalized medicine, omics science thus additionally offers a better understanding of a broader range of drug targets and drug repositioning. Berberine is an isoquinoline alkaloid found in many medicinal plants. We report here a whole genome microarray study in tandem with proteomics techniques for mining the plethora of targets that are putatively involved in the antimicrobial activity of berberine against Escherichia coli. We found DNA replication/repair and transcription to be triggered by berberine, indicating that nucleic acids, in general, are among its targets. Our combined transcriptomics and proteomics multi-omics findings underscore that, in the presence of berberine, cell wall or cell membrane transport and motility-related functions are also specifically regulated. We further report a general decline in metabolism, as seen by repression of genes in carbohydrate and amino acid metabolism, energy production, and conversion. An involvement of multidrug efflux pumps, as well as reduced membrane permeability for developing resistance against berberine in E. coli was noted. Collectively, these findings offer original and significant leads for omics-guided drug discovery and future repositioning approaches in the postgenomics era, using berberine as a multi-omics case study.
Keywords: N-ACETYLTRANSFERASE ACTIVITY; CELL-DIVISION PROTEIN; ESCHERICHIA-COLI; GENE-EXPRESSION; ADDUCT FORMATION; EFFLUX PUMPS; RESISTANCE; BINDING; MEMBRANE; FTSZ